2022
DOI: 10.3389/fmed.2022.825823
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Tele-Instruction Approach Impacts Basic Life Support Performance: A Non-inferiority Trial

Abstract: BackgroundSustaining Basic Life Support (BLS) training during the COVID-19 pandemic bears substantial challenges. The limited availability of highly qualified instructors and tight economic conditions complicates the delivery of these life-saving trainings. Consequently, innovative and resource-efficient approaches are needed to minimize or eliminate contagion while maintaining high training standards and managing learner anxiety related to infection risk.MethodsIn a non-inferiority trial 346 first-year medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…For the important educational outcome of skill performance from end-of-course up to 3 months, (Table 30) we found 13 studies. 423,424,426,427,429-431,433-438 Eleven studies did not find differences for the primary outcomes, 423,424,427,429-431,433-437 but 2 studies found an advantage of 4 steps over 2 steps. 426,438…”
Section: Education Implementation and Teamsmentioning
confidence: 94%
See 1 more Smart Citation
“…For the important educational outcome of skill performance from end-of-course up to 3 months, (Table 30) we found 13 studies. 423,424,426,427,429-431,433-438 Eleven studies did not find differences for the primary outcomes, 423,424,427,429-431,433-437 but 2 studies found an advantage of 4 steps over 2 steps. 426,438…”
Section: Education Implementation and Teamsmentioning
confidence: 94%
“…This SysRev included 16 studies, of which 13 were RCTs [423][424][425][426][427][428][429][430][431][432][433][434][435] and 3 were non-RCTs. [436][437][438] All studies showed a high degree of heterogeneity with respect to skills and populations taught, skill complexity, studentto-instructor ratios, and alternatives that were tested against the classic 4-step approach. Therefore, no metaanalyses could be performed.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Study characteristics, designs, and main outcomes are described in Table 1 . Fourteen studies were RCTs, 12 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 and 3 non-RCTs 34 , 35 , 36 with a total number of 2,906 participants. Publication dates ranged from 2010 to 2022 (with data acquisition between 2004 and 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (82%) were undertaken in Europe, and the studies analyzed nine different skills related to resuscitation. Fourteen studies 12 , 21 , 22 , 24 , 25 , 26 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 reported short term outcomes (up to less than 3 months), while five studies 23 , 27 , 31 , 32 , 35 reported mid- to long-term retention (from 3 months up to 6 months post training). We found a wide range of target populations with 15 studies investigating various groups of healthcare professionals, 12 , 21 , 22 , 23 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 and two studies investigating lay persons 26 , 27 ( Table 1 , Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation